2015
DOI: 10.1515/nsad-2015-0055
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Minors' Gambling on Slot Machines in Finland after the Raising of the Minimum Legal Gambling Age from 15 to 18 Years: A Repeated Cross-Sectional Study

Abstract: Aim The legal gambling age in Finland was raised from 15 to 18 years in 2010, but slot machines were given a transition period that ended with the full law coming into effect on 1 July 2011. The widespread accessibility of slot machines and their popularity among youth led us to consider how age limit was enforced in the Finnish gambling monopoly system and to analyse how underage gambling on slot machines changed after the raising of the minimum age. Methods Two nationwide cross-sectional surveys were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…From the international perspective, Finland is of particular interest due to an exceptional decentralized system of slot machines, which guarantees easy access to these type of games in supermarkets, kiosks, gas stations, cafés etc. The most preferred type of gambling among Finnish underage adolescents is slot machines, and we have shown in our previous study that, regardless of age restriction, approximately 13% of 12-16-year-olds manage to gamble on slot machines (Raisamo et al 2015). So far, underage gambling expenditure has rarely been a subject of specific investigation, and therefore, the present study adds to the scarce body of literature in this field as well.…”
Section: Introductionmentioning
confidence: 67%
“…From the international perspective, Finland is of particular interest due to an exceptional decentralized system of slot machines, which guarantees easy access to these type of games in supermarkets, kiosks, gas stations, cafés etc. The most preferred type of gambling among Finnish underage adolescents is slot machines, and we have shown in our previous study that, regardless of age restriction, approximately 13% of 12-16-year-olds manage to gamble on slot machines (Raisamo et al 2015). So far, underage gambling expenditure has rarely been a subject of specific investigation, and therefore, the present study adds to the scarce body of literature in this field as well.…”
Section: Introductionmentioning
confidence: 67%
“…Age limits are applied in most jurisdictions and studies suggest that they help to reduce problem gambling among youth if set sufficiently high (18 + years) [76, 77]. Restrictions on the working class or other selected groups have commonly been imposed to protect them; also local residents are often not allowed to gamble in casinos in their community.…”
Section: Selective Restrictionsmentioning
confidence: 99%
“…Approximately 20 000 slot machines are not only available in gambling venues but in kiosks, shops, shopping centers, hotels, coffee shops, gas stations where youngsters have access into (Warpenius et al 2012). Based on a population study ( N  = 4566) conducted in 2011, 44 % of 12 to18-year-old Finns had gambled during the past 6 months (Raisamo et al 2013, 2015). Furthermore, a nationwide School Health Promotion Study ( N  = 101,167) conducted in 2010–2011 revealed that 62 % of the 14 to16-year-olds had gambled during the previous year (Räsänen et al 2015).…”
Section: Adolescent Gambling In Finlandmentioning
confidence: 99%